Sistem Informasi Uji KIR Angkutan Umum Berbasis Android Menggunakan Metode Waterfall (Studi Kasus: Dinas Perhubungan Salatiga) - Wicaksono, Mellyuga Errol; Purnomo, Hindriyanto Dwi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Testing or inspection towards a certain motor vehicle are often referred to as a KIR testing. KIR testing is commonly performed by Dinas Perhubungan, a government agency. Usability of KIR testing is to test a vehicle's technical eligibility to decide if a vehicle is either suitable to be used on the road or not. The main goal is to improve the safety for vehicle. On this research, information systems regarding KIR testing towards public transportation were being made. This system information were built on a smartphone using Android operating system. In designing and building applications using the waterfall method, and in testing application using the black box testing method. The data storage system in this study uses Firebase which has been integrated with the application. The result of this research will be an information system in the form of an Android application at Dinas Perhubungan in the City of Salatiga.
Keywords: Android; Black Box Testing; Dinas Perhubungan Salatiga; Firebase; KIR Testing; Waterfall